Temperature and hydrogen-like impurity effects on the excited state of the strong coupling bound polaron in a CsI quantum pseudodot - 肖景林 (Chinese physics B, 2017)
With hydrogen-like impurity（HLI） located in the center of Cs I quantum pseudodot（QPD） and by using the variational method of Pekar type（VMPT）, we investigate the first-excited state energy（FESE）, excitation energy and transition frequency of the strongly-coupled bound polaron in the present paper. Temperature effects on bound polaron properties are calculated by employing the quantum statistical theory（QST）. According to the present work＇s numerical results, the FESE, excitation energy and transition frequency decay（amplify） with raising temperature in the regime of lower（higher）temperature. They are decreasing functions of Coulomb impurity potential strength.